Evaluating exercise therapies in adolescent idiopathic scoliosis: a systematic review with Bayesian network meta-analysis - Yang Jiang; Hao Peng; Yanping Song; Li Huang; Hongbo Chen; Pengcheng Li; Guoshun Yang; Yueyu Song; Qigang Chen; Na Yao (PeerJ)
Background Exercise therapy represents a financially prudent and readily applicable intervention that has gained considerable traction in the treatment of adolescent idiopathic scoliosis (AIS) in recent years. Nevertheless, a definitive agreement on the superiority of one method over another remains elusive. Methods A comprehensive search was performed across the PubMed, Cochrane Library, Embase, and Web of Science databases for randomized controlled trials pertaining to exercise and AIS, concluding on August 20, 2024. Four independent researchers conducted a thorough review of the literature, engaged in meticulous data extraction, and assessed the risk of bias. A Bayesian network meta-analysis was performed utilizing the R programming language (version 4.3.4) and MetaInsight tool (version V6.0.1). Results A total of 23 studies were incorporated into the analysis, encompassing 1,289 participants with AIS. Compared to the control group, the primary meta-analysis showed that both SchrothCo and physiotherapeutic scoliosis-specific exercises (PSSE) modalities significantly improved Cobb angle (MD = −4.79, 95% CI [−8.56 to −1.11] MD = −3.11, 95% CI [−5.27 to −0.9]), axial trunk rotation (ATR) (MD = −3.03, 95% CI [−4.68 to −1.46]; MD = −2.37, 95% CI [−3.59 to −1.14]), and SRS-22 scores (MD = 0.66, 95% CI [0.39–0.94]; MD = 0.44, 95% CI [0.22–0.66]). The secondary meta-analysis showed that within the PSSE modality, Schroth therapy significantly reduced Cobb angle (MD = −2.3, 95% CI [−5.45 to −0.66]), while in the SchrothCo modality, both Schroth + Core and Schroth + Hippotherapy significantly improved Cobb angle (MD = −5.27, 95% CI [−14.15 to −3.5]). For ATR, Schroth therapy within PSSE (MD = −2.79, 95% CI [−6.4 to −0.1]), and Schroth + Core (MD = −4.03, 95% CI [−9.37 to −0.98]), Schroth + Sling (MD = −3.12, 95% CI [−10.05 to −2.94]), and Schroth + Hippotherapy (MD = −3.39, 95% CI [−10.29 to −2.84]) within the SchrothCo modality all showed significant reductions. Significant differences in SRS-22 scores were found only in the PSSE modality with Schroth therapy (MD = 0.48, 95% CI [0.02–0.9]) and in the SchrothCo modality with Schroth + Core (MD = 0.79, 95% CI [0.13–1.43]). Conclusions According to the latest findings, the integration of the Schroth method with core stabilization training (Schroth + Core) is regarded as the optimal strategy for addressing AIS. The integration of core stabilization training with the Schroth method reveals a markedly enhanced effectiveness. Future inquiries should encompass more rigorous studies to establish a more robust evidence foundation and facilitate progress in this domain.